Towards parallel solution of continuous problems by means of a general ﬁnite/spectral–element oriented C/C++ framework - Otero, Alejandro (2010)
In this work, we present the design and implementation of a highly modular and flexible software framework to implement numerical models based on the finite element method (FEM) and its extension to deal with distributed problems. This work improves the current implementation by the adition of parallel calculations capabilities by means of the substructure technique applied to solve problems by the FEM in clusters of computers using the MPI protocol. We considered the solution of a general Poisson problem as a test case to conduct experiments in order to evaluate the scaling capabilities of our code. Conclusions are extracted with focus on future lines of development.